Design of an Insurance Patient Visit Information System Using The V-Model Method - Nunung Mardiah; Fika Nur Afifah; Yuda Syahidin; Irda Sari (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2022)
The objective of this study is to use object-oriented programming to develop an insurance patient visit information system. A qualitative research strategy with a descriptive focus was adopted in this study. A qualitative research strategy with a descriptive focus was adopted in this study. Both observation and a literature review are employed as the data-gathering techniques. Software modeling is done using the Unified Modeling Language and the v-model software development process. The issues identified are as follows: reporting insurance patients is only sometimes ideal, and Delays frequently occur when insurance patient final reports are submitted. The creation of more effective information systems and the use of information technology to create accounts to make them simpler and ensure that the final report of insurance patient visits is not delayed are suggestions made.